37. SPSYCHOLOGICAL URVEY ON SOCIAL STIGMA AND STRESS IN CAREGIVERS OF CHILDREN WITH DISABILITIES IN PHU VANG DISTRICT, HUE CITY (Vietnam Journal of Community Medicine, 2025)
Objectives: To describe social stigma and psychological stress among caregivers of disabled children in Phu Vang district, Hue city, and analyze factors related to psychological stress.Method: A cross-sectional descriptive study of 92 caregivers of children with disabilities aged 0 to under 18 years in Phu Vang district, Hue city. Social stigma and psychological stress of caregivers were assessed using the Social Stigma Scale and DASS-21. Multivariate logistic regression analysis was performed to examine factors associated with psychological stress.Results: The rate of subjects with psychological stress was 47.8%. Factors significantly related to psychological stress (p < 0.05) included: number of disabled children in the family, children with intellectual disabilities, level of disability of children and social stigma of caregivers.Conclusions: Strengthen psychological support and training in skills for caring for children with disabilities for caregivers, to help them reduce psychological burden and provide better care for their children.
Keywords: Social stigma; psychological stress; caregivers; children with disabilities; Phu Vang district